(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Coal mining and coal combustion release environmental contaminants which stay at emission sites for many decades. The paper reports total Se and heavy metals (As, Cd, Cu, Cr, Hg, Pb, Sr, U, V, and Zn) in lettuce, potato, and tissues (liver, kidney, heart, and muscle) of three non-migratory bird species (pigeon, jay, and black coot) from a Raša Bay area (North Adriatic, Croatia). They have presumably been exposed to elevated Se and metal levels in garden soil, surface water, and aquatic sediment contaminated with superhigh-organic-sulphur (SHOS) Raša coal, highly enriched in S, Se, V, and U. Results point at selenium contamination of stream water (up to 78 µg/L total Se in a non-filtered sample), which is well above the Croatian regulatory threshold of 10 µg/L total Se. The stream drains a site of the former coal-separation unit, and an associated bottom sediment contains up to 10.8 mg/kg total Se, which is also above the safe level of 0.60 mg/kg total Se. Moreover, values of Mo, U, V, and Sr, elements commonly elevated in SHOS coal varieties, were also increased in majority of water samples as well as in analysed vegetables, soil, and aquatic sediments. Although Cu, Zn, Pb, and V were slightly increased in liver samples of birds, more in black coot than the other two birds, selenium values were found to be adequate for their normal growth. The fact that Se can be environmentally hazardous and toxic to life, even in small doses, warrants further research on this topic.